Harmonizing the agricultural biotechnology debate for the benefit of African farmers - Kelemu, Segenet; Mahuku, George S.; Fregene, Martin A.; Pachico, Douglas H.; Johnson, Nancy L.; Calvert, Lee A.; Rao, Idupulapati M.; Buruchara, Robin Arani; Amede, Tilahun; Kimani, P.M.; Kirkby, Roger A.; Kaaria, Susan K.; et al. (2003)
The intense debate over agricultural biotechnology is at once fascinating, confusing and disappointing. It is complicated by issues of ethical, moral, socio-economic, political, philosophical and scientific import. Its vocal champions exaggerate their claims of biotechnology as saviour of the poor and hungry, while, equally loudly, its opponents declare it as the doomsday devil of agriculture. Sandwiched between these two camps is the rest of the public, either absorbed or indifferent. Biotechnology issues specific to the African public must include crop and animal productivity, food security, alleviation of poverty and gender equity, and must exclude political considerations. Food and its availability are basic human rights issues—for people without food, everything else is insignificant. Although we should discuss and challenge new technologies and their products, bringing the agricultural biotechnology debate into food aid for Africa where millions are faced with life-or-death situations is irresponsible. Agricultural biotechnology promises the impoverished African a means to improve food security and reduce pressures on the environment, provided the perceived risks associated with the technology are addressed. This paper attempts to harmonize the debate, and to examine the potential benefits and risks that agricultural biotechnology brings to African farmers.